Revision of the genus Tephrochlaena, with a key to genera of Palaearctic Heteromyzinae (Diptera: Heleomyzidae) - Giudice, Giuseppe Lo; Woźnica, Andrzej Józef (Zootaxa, 2020)
In order to fix the identity of the European monospecific genus of heleomyzid flies Tephrochlaena Czerny, 1924 (Figs. 1, 2), the type specimens of Helomyza halterata Meigen, 1830, and Tephrochlaena oraria Collin, 1943, were re-examined. Tephrochlaena oraria is redescribed, the lectotype is designated to clarify the application of the name to the taxon and the type species of Tephrochlaena Czerny, 1924 is fixed as Tephrochlaena oraria Collin, 1943 (= Helomyza halterata sensu Czerny, 1924, nec Meigen, 1830), under ICZN Article 70.3.2. External characters and male and female terminalia are illustrated. A key to the Palaearctic genera of the subfamily Heteromyzinae is provided. By First Reviser action, Tephrochlamys rufiventris (Meigen, 1830) is given precedence over Helomyza halterata Meigen, 1830 syn. nov. under ICZN Article 24.2.1. A lectotype is also designated for Helomyza rufiventris Meigen, 1830 under ICZN Recommendation 73F.